Siebel 7 with DB2 for z/OS : database implementation and administration guide - Anavi-Chaput, Viviane (IBM redbooks., 2003)
In this IBM Redbooks publication, we describe the implementation, customization, and administration of the Siebel 7 database with DB2 UDB for z/OS and OS/390 V7 using AIX V5L or Win2000 Siebel Servers, and we discuss the following topics: Installation tasks for setting up a three-tier configuration, with the application middle tier residing on AIX/Win2000 and the database tier residing on z/OS. The DB2 Connect EE V7 setup required to connect the Siebel application server to the DB2 database on z/OS is also discussed. Customization of the Siebel schema for a production environment. Migration from a development system to a production system. Database administration tasks including: - Monitoring dynamic SQL - Identifying and inactivating unused indexes - Table partitioning - Statistics gathering - Reorg, backup, and recovery Please note that the additional material referenced in the text is not available from IBM.